Inorganic quick-setting filling material and preparation method thereof
By mixing material A and material B at a mass ratio of 1:1, and using the mutual coordination of components such as functional water-soluble resins, the inorganic filling materials are solved by poor fast-cooling effect, insufficient compressive strength, flame retardant and static resistance, which are fire-retardant and static-resistant. The problem of insufficient performance has achieved good rapid condensed effect, high compressive strength and excellent flame retardant and anti-static properties of the material.
Patent Information
- Application Number
- CN202411615364.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-13
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-11-13
AI Technical Summary
The existing inorganic filling materials have poor fast condensed effect, insufficient compressive strength, insufficient flame retardant and anti-static properties, and short service life, making it difficult to meet the needs of filling and reinforcement of coal mine goafs.
Material A and material B are mixed at a 1:1 mass ratio. Material A includes sulfur aluminate cement, blast furnace slag, waste gypsum, recycled alumina fibers and pozzolanum. Material B includes functional water-soluble resin, 3-(N-? lynyl)-2-hydroxypropanesulfonate, sucralose, sodium lignin sulfonate, 1,3,5-triglycidyl-S-triazinetrione and N-(trimethoxysilpropyl)b The sodium diamine triacetate salt improves the fast-coagulation effect and compressive strength of the material through the mutual coordination of these components, while improving the flame retardant and anti-static properties.
It has achieved good rapid condensed effect, high compressive strength, excellent flame retardant and electrostatic properties and long service life of inorganic rapid condensed filling materials, and is suitable for filling and reinforcement of coal mine goafs.
Smart Images

Figure BDA0005132056040000081
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of filling materials, and in particular to an inorganic quick-setting filling material and a preparation method thereof. Background Art
[0002] With the increase in coal mining volume and mining scope, the number of goafs and underground cavities has continued to increase, posing a serious threat to mine safety production, engineering construction, and people's lives and property. At present, the measure adopted by my country is to fill and reinforce goafs and underground cavities. The key to the success of this measure lies in the filling material. The development of filling materials with excellent comprehensive performance and performance stability is crucial to ensure the quality of filling projects.
[0003] At present, the commonly used filling materials are cement slurry injection, organic foam material injection, hydraulic filling, etc. Among them, cement slurry filling, due to the solidification of cement slurry, the volume is reduced, the solidification is slow and water is easy to precipitate, and the filling area is prone to inadequate filling and density; the injection of organic foam material has a good effect, but it is easy to heat up, the material itself is flammable, the price is high, the processing cost is high, and the investment and cost of the enterprise are increased; hydraulic filling materials are transported by pipelines, which limits the maximum particle size of the filling materials, easily leading to pipeline blockage, and the operation process is complicated, the work intensity is high, and the cost is high.
[0004] In order to solve the above problems, a Chinese invention patent with authorization announcement number CN105198346B discloses an inorganic filling material, including material A and material B. Material A is composed of the following parts by mass: 70-80 parts of bauxite powder, 1-2 parts of calcium formate, 15-20 parts of alumina, 2-5 parts of gypsum, 15-20 parts of fly ash, and 2-5 parts of calcium powder; material B is composed of the following parts by mass: 30-40 parts of gypsum, 20-25 parts of lime, 1-2 parts of composite accelerator, 0.1-1 parts of water reducer, 1-5 parts of expansion agent, 0.1-1 parts of sodium dodecyl sulfate, 1-5 parts of polyolefins, and 0.1-1 parts of alkali lignin. The filling body constructed by the invention is in close contact with the surrounding of the tunnel, forming a well-integrated closed body with strong integrity and good compressive resistance. The filling body is expandable, which improves the safety of the mine. It does not burn or support combustion, has outstanding explosion-proof and anti-static properties, and has good gas blocking and fire-fighting effects. It has the advantages of a high filling rate and easier control of the roof, which can effectively control the roof of the goaf and limit the subsidence of the surface. However, the quick-setting effect of the inorganic filling material needs to be further improved, and the compressive strength needs to be further improved.
[0005] It can be seen that the development of an inorganic quick-setting filling material with good quick-setting effect, high compressive strength, good flame retardant and antistatic properties, and long service life and its preparation method meets market demand, has broad market value and application prospects, and is of great significance to promoting the development of the field of thermal insulation materials for RVs. Summary of the invention
[0006] In view of this, the object of the present invention is to provide an inorganic quick-setting filling material with good quick-setting effect, high compressive strength, good flame retardant and antistatic properties, and long service life, and a preparation method thereof.
[0007] In order to achieve the above object, the present invention provides the following technical solutions:
[0008] An inorganic quick-setting filling material comprises material A and material B, wherein the mass ratio of material A to material B is 1:1; material A comprises the following components in parts by weight: 25-35 parts of sulphoaluminate cement, 30-40 parts of blast furnace slag, 10-20 parts of waste gypsum, 1-3 parts of recycled alumina fiber, 5-10 parts of volcanic ash, and 0.8-1.2 parts of (3,6-diaminoacridine-9-yl)boric acid; material B comprises the following raw materials in parts by weight: 4-6 parts of functional water-soluble resin, 3-(N- The functional water-soluble resin comprises 1-2 parts of sodium morpholinyl)-2-hydroxypropanesulfonate, 0.5-0.8 parts of sucralose, 0.1-1 parts of sodium lignin sulfonate, 0.8-1.2 parts of 1,3,5-triglycidyl-S-triazinetrione, and 0.1-0.5 parts of sodium N-(trimethoxysilylpropyl)ethylenediaminetriacetic acid; the functional water-soluble resin comprises structural units introduced by the following monomers: 2-acrylamido-2-methylpropanesulfonic acid, N-trihydroxymethylmethylacrylamide, allyl triphenylphosphonium bromide, and reactive β-cyclodextrin quaternary ammonium salt.
[0009] Preferably, the preparation method of the functional water-soluble resin comprises the following steps: adding 2-acrylamido-2-methylpropanesulfonic acid, N-trihydroxymethyl methacrylamide, allyl triphenylphosphonium bromide, reactive β-cyclodextrin quaternary ammonium salt, and initiator to a high boiling point solvent, stirring and reacting at 60-70° C. in an inert gas atmosphere for 4-6 hours, removing the solvent by rotary evaporation, then dissolving the obtained crude product in water, taking the supernatant and placing it in a dialysis bag, dialyzing it in water for 20-30 hours, and finally taking the supernatant in the dialysis bag, removing water by rotary evaporation to obtain a functional water-soluble resin.
[0010] Preferably, the mass ratio of the 2-acrylamido-2-methylpropanesulfonic acid, N-trimethylolmethylacrylamide, allyl triphenylphosphonium bromide, reactive β-cyclodextrin quaternary ammonium salt, initiator, and high boiling point solvent is 2:2:(0.5-0.8):0.3:(0.05-0.06):(15-25).
[0011] Preferably, there is no special requirement for the source of the reactive β-cyclodextrin quaternary ammonium salt. In one embodiment of the present invention, the reactive β-cyclodextrin quaternary ammonium salt is prepared according to the method of Example 6 of Chinese invention patent with authorization announcement number CN106008755B.
[0012] Preferably, the initiator is azobisisobutyronitrile; the high boiling point solvent is at least one of dimethyl sulfoxide, N,N-dimethylformamide, and N-methylpyrrolidone; and the inert gas is any one of nitrogen, helium, neon, and argon.
[0013] Preferably, the waste gypsum is waste anhydrous gypsum with a fineness of 200-400 mesh.
[0014] Preferably, the fineness of the blast furnace slag is 40-300 mesh.
[0015] Preferably, the sulphoaluminate cement is fast-hardening sulphoaluminate cement, and its 3-day strength is 42.5 MPa.
[0016] Preferably, the particle size of the volcanic ash is 400-800 mesh.
[0017] Preferably, the recycled alumina fiber is recycled alumina continuous fiber F-72, and the monofilament diameter is 7-10 microns.
[0018] Another object of the present invention is to provide a method for preparing the inorganic quick-setting filling material, comprising the following steps: preparing raw materials and components according to a ratio, mixing the components of material A evenly to obtain material A; mixing the raw materials of material B evenly to obtain material B; and packaging them separately; when using, mixing material A and material B evenly in a mass ratio of 1:1, then adding them to water, controlling the water-cement ratio to (0.5-0.75):1, and obtaining the inorganic quick-setting filling material.
[0019] The beneficial effects of adopting the above technical solution are:
[0020] (1) The method for preparing the inorganic quick-setting filling material provided by the present invention is to mix the raw materials and components uniformly by weight. The operation is convenient and easy, the impact on the environment is small, the energy consumption is low, no special equipment and production line are required, the preparation efficiency and the qualified rate of finished products are high, and the method is suitable for continuous large-scale production, and has a high value for promotion and application.
[0021] (2) The inorganic quick-setting filling material provided by the present invention comprises material A and material B, wherein the mass ratio of material A to material B is 1:1; the material A comprises the following components in parts by weight: 25-35 parts of sulphoaluminate cement, 30-40 parts of blast furnace slag, 10-20 parts of waste gypsum, 1-3 parts of recycled alumina fiber, 5-10 parts of volcanic ash, and 0.8-1.2 parts of (3,6-diaminoacridine-9-yl) boric acid; the material B comprises the following raw materials in parts by weight: functional water-soluble 4-6 parts of active resin, 1-2 parts of 3-(N-morpholinyl)-2-hydroxypropanesulfonate sodium, 0.5-0.8 parts of sucralose, 0.1-1 parts of sodium lignin sulfonate, 0.8-1.2 parts of 1,3,5-triglycidyl-S-triazinetrione, 0.1-0.5 parts of N-(trimethoxysilylpropyl)ethylenediaminetriacetic acid sodium salt; through the mutual cooperation between the components, the prepared inorganic quick-setting filling material has good quick-setting effect, high compressive strength, good flame retardant and antistatic properties, and long service life.
[0022] (3) The inorganic quick-setting filling material provided by the present invention comprises a structural unit introduced by the following monomers: 2-acrylamide-2-methylpropanesulfonic acid, N-trihydroxymethyl methacrylamide, allyl triphenylphosphonium bromide, and reactive β-cyclodextrin quaternary ammonium salt; sulfonic acid group, phenylphosphonium bromide, β-cyclodextrin quaternary ammonium salt, hydroxymethyl group, and amide group structure are simultaneously introduced into the molecular structure of the functional water-soluble resin. These structures can effectively improve the quick-setting effect under the multiple effects of electronic effect, steric effect, and conjugation effect. After the material is poured into the broken coal rock mass and the goaf, it has good diffusion and permeability. While ensuring high water retention, it can form a dense consolidation body with the coal body, and it has high compressive strength, good filling effect, pressure-bearing density, and good plugging performance. The use of blast furnace slag, waste gypsum, and recycled alumina fiber belongs to the recycling and reuse of waste, realizing the transformation of waste into treasure, which can not only save resources but also be beneficial to environmental protection. Moreover, through the combined use of the above components, the product can be endowed with excellent mechanical strength and plugging performance; working in conjunction with other components and raw materials, it can resolve the destructive effects of the external environment on the filling material structure, improve the density of the internal structure, and further improve the comprehensive performance and performance stability of the filling material. DETAILED DESCRIPTION
[0023] In order to make the technical solution of the present invention better understood by the technical personnel in the field, and to make the above-mentioned features, purposes and advantages of the present invention more clearly understood, the present invention is further described below in conjunction with the embodiments. The embodiments are only used to illustrate the present invention and are not used to limit the scope of the present invention.
[0024] Example 1
[0025] An inorganic quick-setting filling material, comprising material A and material B, wherein the mass ratio of material A to material B is 1:1; the material A comprises the following components in parts by weight: 25 parts of sulphoaluminate cement, 30 parts of blast furnace slag, 10 parts of waste gypsum, 1 part of recycled alumina fiber, 5 parts of volcanic ash, and 0.8 parts of (3,6-diaminoacridine-9-yl)boric acid; the material B comprises the following raw materials in parts by weight: 4 parts of functional water-soluble resin, 3-(N-morpholine The functional water-soluble resin comprises 1 part of sodium (1,3,5-triglycidyl)-2-hydroxypropanesulfonate, 0.5 part of sucralose, 0.1 part of sodium lignin sulfonate, 0.8 part of 1,3,5-triglycidyl-S-triazinetrione, and 0.1 part of sodium N-(trimethoxysilylpropyl)ethylenediaminetriacetic acid; the functional water-soluble resin comprises structural units introduced by the following monomers: 2-acrylamido-2-methylpropanesulfonic acid, N-trihydroxymethylmethylacrylamide, allyl triphenylphosphonium bromide, and reactive β-cyclodextrin quaternary ammonium salt.
[0026] The preparation method of the functional water-soluble resin comprises the following steps: adding 2-acrylamide-2-methylpropanesulfonic acid, N-trihydroxymethyl methacrylamide, allyl triphenylphosphonium bromide, reactive beta-cyclodextrin quaternary ammonium salt and initiator into a high boiling point solvent, stirring and reacting at 60°C for 4 hours in an inert gas atmosphere, removing the solvent by rotary evaporation, then dissolving the obtained crude product in water, taking the supernatant and placing it in a dialysis bag, dialysing it in water for 20-30 hours, and finally taking the supernatant in the dialysis bag, removing water by rotary evaporation to obtain the functional water-soluble resin; the 2-acrylamide-2-methylpropanesulfonic acid The mass ratio of 1,2-propanesulfonic acid, N-trimethylolmethyl acrylamide, allyl triphenylphosphonium bromide, reactive β-cyclodextrin quaternary ammonium salt, initiator, and high boiling point solvent is 2:2:0.5:0.3:0.05:15; the reactive β-cyclodextrin quaternary ammonium salt is prepared according to the method of Example 6 of the Chinese invention patent with authorization announcement number CN106008755B; the initiator is azobisisobutyronitrile; the high boiling point solvent is dimethyl sulfoxide; the inert gas is nitrogen; through GPC test, the number average molecular weight of the resin is 18110 g / mol, M W / M n =1.313; through elemental analysis and weight change calculation, the mass ratio of the structural units introduced by 2-acrylamido-2-methylpropanesulfonic acid, N-trimethylolmethylacrylamide, allyl triphenylphosphonium bromide, and reactive β-cyclodextrin quaternary ammonium salt is 1.98:2:0.49:0.27;
[0027] The waste gypsum is waste anhydrous hard gypsum with a fineness of 200 mesh; the fineness of the blast furnace slag is 40 mesh; the sulphoaluminate cement is fast-hardening sulphoaluminate cement with a 3-day strength of 42.5 MPa; the particle size of the volcanic ash is 400 mesh; the recycled alumina fiber is recycled alumina continuous fiber F-72 with a single fiber diameter of 7-10 microns.
[0028] A preparation method of the inorganic quick-setting filling material comprises the following steps: preparing raw materials and components according to a proportion, mixing the components of material A evenly to obtain material A; mixing the raw materials of material B evenly to obtain material B; and packaging them separately; when using, mixing material A and material B evenly in a mass ratio of 1:1, then adding them into water, controlling the water-cement ratio to 0.75:1, and obtaining the inorganic quick-setting filling material.
[0029] Example 2
[0030] An inorganic quick-setting filling material, comprising material A and material B, wherein the mass ratio of material A to material B is 1:1; material A comprises the following components in parts by weight: 27 parts of sulphoaluminate cement, 33 parts of blast furnace slag, 12 parts of waste gypsum, 1.5 parts of recycled alumina fiber, 6 parts of volcanic ash, and 0.9 parts of (3,6-diaminoacridine-9-yl)boric acid; material B comprises the following raw materials in parts by weight: 4.5 parts of functional water-soluble resin, 3-(N-morpholino)pyrrolidone, 4 ... The functional water-soluble resin comprises 1.2 parts of sodium (1,3,5-triglycidyl)-2-hydroxypropanesulfonate, 0.6 parts of sucralose, 0.5 parts of sodium lignin sulfonate, 0.9 parts of 1,3,5-triglycidyl-S-triazinetrione, and 0.2 parts of sodium N-(trimethoxysilylpropyl)ethylenediaminetriacetic acid; the functional water-soluble resin comprises structural units introduced by the following monomers: 2-acrylamido-2-methylpropanesulfonic acid, N-trihydroxymethylmethylacrylamide, allyl triphenylphosphonium bromide, and reactive β-cyclodextrin quaternary ammonium salt.
[0031] The preparation method of the functional water-soluble resin comprises the following steps: adding 2-acrylamido-2-methylpropanesulfonic acid, N-trihydroxymethyl methacrylamide, allyl triphenylphosphonium bromide, reactive beta-cyclodextrin quaternary ammonium salt and initiator into a high boiling point solvent, stirring and reacting at 63°C for 4.5 hours in an inert gas atmosphere, removing the solvent by rotary evaporation, then dissolving the obtained crude product in water, taking the supernatant and placing it in a dialysis bag, dialysing it in water for 23 hours, and finally taking the supernatant in the dialysis bag, removing water by rotary evaporation to obtain the functional water-soluble resin; The mass ratio of 2-acrylamido-2-methylpropanesulfonic acid, N-trihydroxymethyl methacrylamide, allyl triphenylphosphonium bromide, reactive β-cyclodextrin quaternary ammonium salt, initiator, and high boiling point solvent is 2:2:0.6:0.3:0.053:17; the reactive β-cyclodextrin quaternary ammonium salt is prepared according to the method of Example 6 of the Chinese invention patent with authorization announcement number CN106008755B; the initiator is azobisisobutyronitrile; the high boiling point solvent is N,N-dimethylformamide; and the inert gas is helium.
[0032] The waste gypsum is waste anhydrous hard gypsum with a fineness of 250 mesh; the fineness of the blast furnace slag is 150 mesh; the sulphoaluminate cement is fast-hardening sulphoaluminate cement with a 3-day strength of 42.5 MPa; the particle size of the volcanic ash is 500 mesh; the recycled alumina fiber is recycled alumina continuous fiber F-72 with a single filament diameter of 7-10 microns.
[0033] A preparation method of the inorganic quick-setting filling material comprises the following steps: preparing raw materials and components according to a proportion, mixing the components of material A evenly to obtain material A; mixing the raw materials of material B evenly to obtain material B; and packaging them separately; when using, mixing material A and material B evenly in a mass ratio of 1:1, then adding them into water, controlling the water-cement ratio to 0.7:1, and obtaining the inorganic quick-setting filling material.
[0034] Example 3
[0035] An inorganic quick-setting filling material, comprising material A and material B, wherein the mass ratio of material A to material B is 1:1; the material A comprises the following components in parts by weight: 30 parts of sulphoaluminate cement, 35 parts of blast furnace slag, 15 parts of waste gypsum, 2 parts of recycled alumina fiber, 7 parts of volcanic ash, and 1 part of (3,6-diaminoacridine-9-yl)boric acid; the material B comprises the following raw materials in parts by weight: 5 parts of functional water-soluble resin, 3-(N-morpholinyl) -1.5 parts of sodium 2-hydroxypropanesulfonate, 0.65 parts of sucralose, 0.7 parts of sodium lignin sulfonate, 1 part of 1,3,5-triglycidyl-S-triazinetrione, and 0.35 parts of sodium N-(trimethoxysilylpropyl)ethylenediaminetriacetic acid; the functional water-soluble resin includes structural units introduced by the following monomers: 2-acrylamido-2-methylpropanesulfonic acid, N-trihydroxymethyl methacrylamide, allyl triphenylphosphonium bromide, and reactive β-cyclodextrin quaternary ammonium salt.
[0036] The preparation method of the functional water-soluble resin comprises the following steps: adding 2-acrylamido-2-methylpropanesulfonic acid, N-trihydroxymethyl methacrylamide, allyl triphenylphosphonium bromide, reactive beta-cyclodextrin quaternary ammonium salt and initiator into a high boiling point solvent, stirring and reacting at 65°C for 5 hours in an inert gas atmosphere, removing the solvent by rotary evaporation, then dissolving the obtained crude product in water, taking the supernatant and placing it in a dialysis bag, dialyzing it in water for 25 hours, and finally taking the supernatant in the dialysis bag, removing water by rotary evaporation to obtain the functional water-soluble resin; The mass ratio of 2-acrylamido-2-methylpropanesulfonic acid, N-trihydroxymethyl methacrylamide, allyl triphenylphosphonium bromide, reactive β-cyclodextrin quaternary ammonium salt, initiator, and high boiling point solvent is 2:2:0.65:0.3:0.055:20; the reactive β-cyclodextrin quaternary ammonium salt is prepared according to the method of Example 6 of the Chinese invention patent with authorization announcement number CN106008755B; the initiator is azobisisobutyronitrile; the high boiling point solvent is N-methylpyrrolidone; and the inert gas is neon.
[0037] The waste gypsum is waste anhydrous hard gypsum with a fineness of 300 mesh; the fineness of the blast furnace slag is 200 mesh; the sulphoaluminate cement is fast-hardening sulphoaluminate cement, and its 3-day strength is 42.5 MPa; the particle size of the volcanic ash is 600 mesh; the recycled alumina fiber is recycled alumina continuous fiber F-72, and the single fiber diameter is 7-10 microns.
[0038] A preparation method of the inorganic quick-setting filling material comprises the following steps: preparing raw materials and components according to a proportion, mixing the components of material A evenly to obtain material A; mixing the raw materials of material B evenly to obtain material B; and packaging them separately; when using, mixing material A and material B evenly in a mass ratio of 1:1, then adding them into water, controlling the water-cement ratio to 0.6:1, and obtaining the inorganic quick-setting filling material.
[0039] Example 4
[0040] An inorganic quick-setting filling material, comprising material A and material B, wherein the mass ratio of material A to material B is 1:1; the material A comprises the following components in parts by weight: 33 parts of sulphoaluminate cement, 38 parts of blast furnace slag, 18 parts of waste gypsum, 2.5 parts of recycled alumina fiber, 9 parts of volcanic ash, and 1.1 parts of (3,6-diaminoacridine-9-yl)boric acid; the material B comprises the following raw materials in parts by weight: 5.5 parts of functional water-soluble resin, 3-(N-morpholine The functional water-soluble resin comprises 1.8 parts of sodium (1,3,5-triglycidyl)-2-hydroxypropanesulfonate, 0.75 parts of sucralose, 0.9 parts of sodium lignin sulfonate, 1.1 parts of 1,3,5-triglycidyl-S-triazinetrione, and 0.4 parts of sodium N-(trimethoxysilylpropyl)ethylenediaminetriacetic acid; the functional water-soluble resin comprises structural units introduced by the following monomers: 2-acrylamido-2-methylpropanesulfonic acid, N-trihydroxymethylmethylacrylamide, allyl triphenylphosphonium bromide, and reactive β-cyclodextrin quaternary ammonium salt.
[0041] The preparation method of the functional water-soluble resin comprises the following steps: adding 2-acrylamide-2-methylpropanesulfonic acid, N-trihydroxymethyl methacrylamide, allyl triphenylphosphonium bromide, reactive beta-cyclodextrin quaternary ammonium salt and an initiator into a high boiling point solvent, stirring and reacting at 68°C for 5.5 hours in an inert gas atmosphere, removing the solvent by rotary evaporation, then dissolving the obtained crude product in water, taking the supernatant and placing it in a dialysis bag, dialysing it in water for 28 hours, finally taking the supernatant in the dialysis bag, removing water by rotary evaporation, and obtaining the functional water-soluble resin; the 2-acrylamide-2-methylpropanesulfonic acid The mass ratio of acid, N-trimethylolmethyl acrylamide, allyl triphenylphosphonium bromide, reactive β-cyclodextrin quaternary ammonium salt, initiator, and high boiling point solvent is 2:2:0.75:0.3:0.058:23; the reactive β-cyclodextrin quaternary ammonium salt is prepared according to the method of Example 6 of the Chinese invention patent with authorization announcement number CN106008755B; the initiator is azobisisobutyronitrile; the high boiling point solvent is a mixture of dimethyl sulfoxide, N,N-dimethylformamide, and N-methylpyrrolidone in a mass ratio of 1:2:3; and the inert gas is nitrogen.
[0042] The waste gypsum is waste anhydrous hard gypsum with a fineness of 350 mesh; the fineness of the blast furnace slag is 280 mesh; the sulphoaluminate cement is fast-hardening sulphoaluminate cement with a 3-day strength of 42.5 MPa; the particle size of the volcanic ash is 750 mesh; the recycled alumina fiber is recycled alumina continuous fiber F-72 with a single filament diameter of 7-10 microns.
[0043] A preparation method of the inorganic quick-setting filling material comprises the following steps: preparing raw materials and components according to a proportion, mixing the components of material A evenly to obtain material A; mixing the raw materials of material B evenly to obtain material B; and packaging them separately; when using, mixing material A and material B evenly in a mass ratio of 1:1, then adding them into water, controlling the water-cement ratio to 0.55:1, and obtaining the inorganic quick-setting filling material.
[0044] Example 5
[0045] An inorganic quick-setting filling material, comprising material A and material B, wherein the mass ratio of material A to material B is 1:1; material A comprises the following components in parts by weight: 35 parts of sulphoaluminate cement, 40 parts of blast furnace slag, 20 parts of waste gypsum, 3 parts of recycled alumina fiber, 10 parts of volcanic ash, and 1.2 parts of (3,6-diaminoacridine-9-yl)boric acid; material B comprises the following raw materials in parts by weight: 6 parts of functional water-soluble resin, 3-(N-morpholino)pyrrolidone, 1.2 parts of sulphoaluminate cement, 35 parts of sulphoaluminate cement, 40 parts of blast furnace slag, 20 parts of waste gypsum, 3 parts of recycled alumina fiber, 10 parts of volcanic ash, and 1.2 parts of (3,6-diaminoacridine-9-yl)boric acid; The functional water-soluble resin comprises 2 parts of sodium 2-hydroxypropanesulfonate (poly(2-(1-(2-(((((((((((((((((((-((-(-(-1-(-2-(-(-(-(-(-(-(-(-(-(-(-(-(-(-(-(-(-(-(-(-(-(-(-(-(-(-(-(-(-(-(-(-(-(-(-(-(-(-(-(-(-(-(-(-(-(-(-(-(-(-(-(-(-(-(-(-(-(-(-(-(-
[0046] The preparation method of the functional water-soluble resin comprises the following steps: adding 2-acrylamido-2-methylpropanesulfonic acid, N-trihydroxymethyl methacrylamide, allyl triphenylphosphonium bromide, reactive beta-cyclodextrin quaternary ammonium salt and initiator into a high boiling point solvent, stirring and reacting at 70°C for 6 hours in an inert gas atmosphere, removing the solvent by rotary evaporation, then dissolving the obtained crude product in water, taking the supernatant and placing it in a dialysis bag, dialysing it in water for 30 hours, and finally taking the supernatant in the dialysis bag, removing water by rotary evaporation to obtain the functional water-soluble resin. ; The mass ratio of the 2-acrylamido-2-methylpropanesulfonic acid, N-trimethylolmethylacrylamide, allyl triphenylphosphonium bromide, reactive β-cyclodextrin quaternary ammonium salt, initiator, and high boiling point solvent is 2:2:0.8:0.3:0.06:25; the reactive β-cyclodextrin quaternary ammonium salt is prepared according to the method of Example 6 of the Chinese invention patent with authorization announcement number CN106008755B; the initiator is azobisisobutyronitrile; the high boiling point solvent is dimethyl sulfoxide; and the inert gas is neon.
[0047] The waste gypsum is waste anhydrous hard gypsum with a fineness of 400 mesh; the fineness of the blast furnace slag is 300 mesh; the sulphoaluminate cement is fast-hardening sulphoaluminate cement, and its 3-day strength is 42.5 MPa; the particle size of the volcanic ash is 800 mesh; the recycled alumina fiber is recycled alumina continuous fiber F-72, and the single fiber diameter is 7-10 microns.
[0048] A preparation method of the inorganic quick-setting filling material comprises the following steps: preparing raw materials and components according to a proportion, mixing the components of material A evenly to obtain material A; mixing the raw materials of material B evenly to obtain material B; and packaging them separately; when using, mixing material A and material B evenly in a mass ratio of 1:1, then adding them into water, controlling the water-cement ratio to 0.5:1, and obtaining the inorganic quick-setting filling material.
[0049] Comparative Example 1
[0050] An inorganic quick-setting filling material and a preparation method thereof, which are basically the same as those of Example 1, except that no functional water-soluble resin is added and no alumina fiber is recycled.
[0051] Comparative Example 2
[0052] An inorganic quick-setting filling material and a preparation method thereof, which are substantially the same as those of Example 1, except that (3,6-diaminoacridine-9-yl)boric acid and sodium 3-(N-morpholinyl)-2-hydroxypropanesulfonate are not added.
[0053] The inorganic quick-setting filling materials described in Examples 1-5 and Comparative Examples 1-2 were subjected to performance tests. The test results are shown in Table 1. The test methods refer to the current national standards and conventional methods in the industry: the antistatic performance test is the surface resistance of the material after curing for 7 days, the laboratory temperature is 22°C, the relative humidity is 64%, and the flame retardancy is measured by the flame burning time in the alcohol burner combustion experiment. The smaller the value, the better the flame retardancy.
[0054] It can be seen from Table 1 that the inorganic quick-setting filling material disclosed in the embodiment of the present invention has better compressive strength, quick-setting performance and flame retardancy and antistatic properties than the comparative example; the combined use of functional water-soluble resin, recycled alumina fiber, (3,6-diaminoacridine-9-yl)boric acid and 3-(N-morpholinyl)-2-hydroxypropanesulfonate sodium is beneficial to improving the above properties.
[0055] Table 1
[0056]
[0057] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The above embodiments and descriptions only describe the principles of the present invention. The present invention may be subject to various changes and improvements without departing from the spirit and scope of the present invention. These changes and improvements fall within the scope of the present invention. The scope of protection claimed by the present invention is defined by the attached claims and their equivalents.
Claims
1. An inorganic quick-setting filling material, characterized in that: The invention comprises material A and material B, wherein the mass ratio of material A to material B is 1:1; the material A comprises the following components in parts by weight: 25-35 parts of sulphoaluminate cement, 30-40 parts of blast furnace slag, 10-20 parts of waste gypsum, 1-3 parts of recycled alumina fiber, 5-10 parts of volcanic ash, and 0.8-1.2 parts of (3,6-diaminoacridine-9-yl)boric acid; the material B comprises the following raw materials in parts by weight: 4-6 parts of functional water-soluble resin, 3-(N-morpholinyl)-2 -1-2 parts of sodium hydroxypropane sulfonate, 0.5-0.8 parts of sucralose, 0.1-1 parts of sodium lignin sulfonate, 0.8-1.2 parts of 1,3,5-triglycidyl-S-triazinetrione, and 0.1-0.5 parts of sodium N-(trimethoxysilylpropyl)ethylenediaminetriacetic acid; the functional water-soluble resin includes structural units introduced by the following monomers: 2-acrylamido-2-methylpropane sulfonic acid, N-trihydroxymethyl methacrylamide, allyl triphenylphosphonium bromide, and reactive β-cyclodextrin quaternary ammonium salt.
2. The inorganic quick-setting filling material according to claim 1, characterized in that: The preparation method of the functional water-soluble resin comprises the following steps: adding 2-acrylamide-2-methylpropanesulfonic acid, N-trihydroxymethyl methacrylamide, allyl triphenylphosphonium bromide, reactive beta-cyclodextrin quaternary ammonium salt and an initiator into a high boiling point solvent, stirring and reacting at 60-70° C. for 4-6 hours in an inert gas atmosphere, removing the solvent by rotary evaporation, then dissolving the obtained crude product in water, taking the supernatant and placing it in a dialysis bag, dialysing it in water for 20-30 hours, and finally taking the supernatant in the dialysis bag, removing water by rotary evaporation to obtain the functional water-soluble resin.
3. The inorganic quick-setting filling material according to claim 2, characterized in that: The mass ratio of the 2-acrylamido-2-methylpropanesulfonic acid, N-trimethylolmethylacrylamide, allyl triphenylphosphonium bromide, reactive β-cyclodextrin quaternary ammonium salt, initiator and high boiling point solvent is 2:2:(0.5-0.8):0.3:(0.05-0.06):(15-25).
4. The inorganic quick-setting filling material according to claim 2, characterized in that: The initiator is azobisisobutyronitrile; the high boiling point solvent is at least one of dimethyl sulfoxide, N,N-dimethylformamide, and N-methylpyrrolidone; and the inert gas is any one of nitrogen, helium, neon, and argon.
5. The inorganic quick-setting filling material according to claim 1, characterized in that: The waste gypsum is waste anhydrous gypsum with a fineness of 200-400 meshes.
6. The inorganic quick-setting filling material according to claim 1, characterized in that: The fineness of the blast furnace slag is 40-300 meshes.
7. The inorganic quick-setting filling material according to claim 1, characterized in that: The sulphoaluminate cement is a fast-hardening sulphoaluminate cement, and its 3-day strength is 42.5 MPa.
8. The inorganic quick-setting filling material according to claim 1, characterized in that: The particle size of the volcanic ash is 400-800 meshes.
9. The inorganic quick-setting filling material according to claim 1, characterized in that: The recycled alumina fiber is recycled alumina continuous fiber F-72, and the single fiber diameter is 7-10 microns.
10. A method for preparing the inorganic quick-setting filling material according to any one of claims 1 to 9, characterized in that: The method comprises the following steps: preparing raw materials and components according to a ratio, mixing the components of material A evenly to obtain material A; mixing the raw materials of material B evenly to obtain material B; and packaging them respectively; When in use, material A and material B are evenly mixed in a mass ratio of 1:1, and then added into water, and the water-cement ratio is controlled to be (0.5-0.75):1 to obtain an inorganic quick-setting filling material.
Citation Information
Patent Citations
An inorganic filling material
CN105198346B
A reactive β-cyclodextrin quaternary ammonium salt, its preparation method and application
CN106008755B
Road repair grout material and preparation method thereof
CN106045427A
High-strength waterproof concrete and preparation method thereof
CN116655327A
Anti-cracking concrete and preparation method thereof
CN116730681A
Cited By
Alkali-free accelerator and preparation method thereof
CN120040107A
Mining high-strength quick-setting cement grouting material and preparation method thereof
CN121021101A